2022
DOI: 10.3390/ph15030362
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Role of miR-342-5p and miR-491-5p in Human Osteosarcoma Cells

Abstract: Osteosarcomas are the most common type of malignant bone tumor. These tumors are characterized by the synthesis of an osteoid matrix. Current treatments are based on surgery and combination chemotherapy. However, for metastatic or recurrent tumors, chemotherapy is generally ineffective, and osteosarcomas are sometimes unresectable. Thus, the use of microRNAs (miRNAs) may represent an attractive alternative for the development of new therapies. Using high-throughput functional screening based on impedancemetry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 40 publications
6
16
1
Order By: Relevance
“…The miRNAs in uence cancer cell initiation and metastasis [35] Our ndings show rst evidence that miR-342-5p is an important regulator in HCC resistance. miR-342-5p has been reported to be a potential tumor suppressor in neuroblastoma [36][37][38]. miR-342-5p mediated targeting of NAA10 suppresses colon cancer growth and induces apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs in uence cancer cell initiation and metastasis [35] Our ndings show rst evidence that miR-342-5p is an important regulator in HCC resistance. miR-342-5p has been reported to be a potential tumor suppressor in neuroblastoma [36][37][38]. miR-342-5p mediated targeting of NAA10 suppresses colon cancer growth and induces apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR phosphorylation is involved in the migration and invasion of OS mediated by Circular RNA cir-ITCH [ 36 ]. What’s more, it’s also researched that tumor-suppressive activity in OS is correlative with the downregulation of EGFR [ 37 , 38 ]. Through validation of target protein in the GEO dataset, we obtained SATB2 protein target exhibiting strong interaction with formononetin.…”
Section: Discussionmentioning
confidence: 99%
“…Growing chondrosarcoma and osteosarcoma cells were seeded at 1x10 4 cells/cm 2 per 25 cm 2 flask. Cell lines were transfected 24 h after seeding with 20 nM of miRNA mimics using INTERFERin™ (Polyplus-Transfection) as described previously ( 26 , 27 ). An additional CDDP treatment was carried out after 48 h with each sublethal dose of CDDP as described previously ( 26 , 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…One study has shown that pharmacological inhibition of Bcl-xL improves the sensitivity of osteosarcoma to doxorubicin ( 25 ). Furthermore, we previously showed that the direct inhibition of Bcl-xL by miR-491-5p and miR-342-5p induces apoptosis on osteosarcoma and chondrosarcoma cell lines ( 26 , 27 ). MiR-342-5p also directly inhibited the expression of Bcl-2 in some tested cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation